The Influence of Technology Readiness, Strategic Leadership, and Organizational Change on Organizational Performance in the Indonesian Navy - Kalambo, Yohanis; Anggiani, Sarfilianty; Usman, Bahtiar (ADPEBI International Journal of Business and Social Science, 2024)
Purpose – This research aims to analyze the influence of Technology Readiness, Strategic Leadership, and Organizational Change on Organizational Performance mediated by Competency Development in the Indonesian Navy. Methodology/approach –This research method used quantitative approach, tested using Structural. Equation Modelling-Analysis of Moment Structures (SEM-AMOS). The sampling method uses nonprobability sampling with a subjective sampling procedure or sampling using a purposive sampling technique, by taking data from 330 Indonesian Navy officers who served for a minimum 5 years in the Indonesian Navy. Findings – The findings in this research there is positive influence of Technology Readiness on Organizational Performance, Strategic Leadership on Competency Development, Organizational Change on Organizational Performance, Organizational Change on Competency Development, Competency Development on Organizational Performance, and Organizational Change on Organizational Performance which is mediated by Competency Development. Novelty/value –The TNI AL (Indonesian Navy) organization tries to adapt to technological developments and changes in the strategic environment by making changes to its organization. Effective organizational change correlates with better organizational performance. Apart from that, a positive influence founded between Organizational Change on Organizational Performance which mediated by Competency Development. Organizational Change as a form of organizational adaptation, if followed by appropriate Competency Development policies, will encourage the enhancement of Indonesian Navy (TNI-AL) Organizational Performance.